(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Utilisation of energy from renewable sources can bring great positive ecological effects. The greatest hope related to renewable sources of energy is with biomass, the stocks of which present huge reserves of energy. Biomass can be used for energy purposes in the process of direct incinerating of bio-fuels (timber, straw seed, hay) or in the form of gas.In this paper, described are the economical effects of pro-ecological enterprises dealing with energy. Described is the example of biomass application and presented is its efficiency.